Nucleotide sequence analysis of genes encoding a toluene/benzene-2-monooxygenase from Pseudomonas sp. strain JS150. - Johnson, G R (1995)
It was previously shown by others that Pseudomonas sp. strain JS150 metabolizes benzene and alkyl- and chloro-substituted benzenes by using dioxygenase-initiated pathways coupled with multiple downstream metabolic pathways to accommodate catechol metabolism. By cloning genes encoding benzene-degradative enzymes, we found that strain JS150 also carries genes for a toluene/benzene-2-monooxygenase. The gene cluster encoding a 2-monooxygenase and its cognate regulator was cloned from a plasmid carried by strain JS150. Oxygen (18O2) incorporation experiments using Pseudomonas aeruginosa strains that carried the cloned genes confirmed that toluene hydroxylation was catalyzed through an authentic monooxygenase reaction to yield ortho-cresol. Regions encoding the toluene-2-monooxygenase and regulatory gene product were localized in two regions of the cloned fragment. The nucleotide sequence of the toluene/benzene-2-monooxygenase locus was determined. Analysis of this sequence revealed six open reading frames that were then designated tbmA, tbmB, tbmC, tbmD, tbmE, and tbmF. The deduced amino acid sequences for these genes showed the presence of motifs similar to well-conserved functional domains of multicomponent oxygenases. This analysis allowed the tentative identification of two terminal oxygenase subunits (TbmB and TbmD) and an electron transport protein (TbmF) for the monooxygenase enzyme. In addition to these gene products, all the tbm polypeptides shared significant homology with protein components from other bacterial multicomponent monooxygenases. Overall, the tbm gene products shared greater similarity with polypeptides from the phenol hydroxylases of Pseudomonas putida CF600, P35X, and BH than with those from the toluene monooxygenases of Pseudomonas mendocina KR1 and Burkholderia (Pseudomonas) pickettii PKO1. The relationship found between the phenol hydroxylases and a toluene-2-monooxygenase, characterized in this study for the first time at the nucleotide sequence level, suggested that DNA probes used for surveys of environmental populations should be carefully selected to reflect DNA sequences corresponding to the metabolic pathway of interest.